Romanian legal management rules limit wood production in Norway spruce and beech forests - Olivier Bouriaud; Gheorghe Marin; Laura Bouriaud; Dominik Hessenmöller; Ernst-Detlef Schulze (Forest Ecosystems, 2016)
Background The quantitative impact of forest management on forests’ wood resource was evaluated for Picea and Fagus mixed forests. The effects on the productivity of tendering operations, thinnings and rotation length have seldom been directly quantified on landscape scale.